Personal Protective Footwear and The Risk of Tinea Unguium among Lojejer Villager Farmers - Iftinan, Karenzha; Raharjo, Angga Mardro; Agustina, Dini; Mufida, Diana Chusna (Universitas Airlangga, 2025)
Introduction: Tinea unguium is a nail infection caused by dermatophytes, characterized by nail discoloration, thickening, and brittleness. Farmers, often exposed to prolonged wet conditions, are at higher risk of this infection. The use of appropriate footwear is recommended to mitigate this risk. However, inadequate personal protective equipment (PPE) usage makes farmers more susceptible to Tinea unguium. Research on Tinea unguium among farmers in Lojejer Village is limited, with differing result on the link between wearing footwear as PPE and the occurance of Tinea unguium. This study aimed to investigate the relationship between the use of footwear as PPE and the incidence of Tinea unguium among farmers in Lojejer Village. Methods: This study uses a cross-sectional observational design. It involved 98 respondents determined using Slovin’s formula. Data were collected through interviews and nail samples, which were subjected to fungal culture on sabouraud dextrose agar (SDA) medium and microscopic examination with lactophenol cotton blue staining. Fisher’s Exact tests were used for analysis. Results: Results revealed that seven farmers (7.14%) were affected by Tinea unguium, predominantly males (85.8%) aged 45–64 years (57.1%). Trichophyton rubrum was identified as the primary dermatophyte, with Aspergillus sp. as a contaminant. Statistical analysis showed no significant relationship between footwear usage, personal hygiene, or footwear hygiene and Tinea unguium (p-values > 0.05). Conclusion: The study found no significant association between footwear use, hpersonal hygiene, and footwear hygiene with Tinea unguium incidence among farmers in Lojejer Village